PHYTOCHEMICAL CONSTITUENTS AND INVITRO FREE RADICAL SCAVENGING ACTIVITIES OF METHANOL EXTRACT AND FRACTIONS OF Ficus platyphylla LEAVES (MORACEAE) - Shemishere, Ufuoma Bigila; Turaki, Aliyu Abdullahi; Yusuf, Abdulrahman Bashir; Anyebe, Daniel Abu; Erhovwosere, Oghenevwede; Aghayere, Faith; Taiwo, Judith Enuwamagbe (FUDMA JOURNAL OF SCIENCES, 2023)
The demand for plant-based antioxidants is expanding rapidly due to their effectiveness and accessibility. This study examined the phytochemical constituent and in vitro free radical scavenging activities of Methanol extract and fractions of Ficus platyphylla leaves. Standard known methods were used to determine the qualitative and quantitative phytochemical constituents and free radical scavenging activities of the extract and fractions of the plant dried leaves. Methanol extraction produced a yield of 12.64%. Qualitative phytochemical screening confirmed the presence of alkaloids in the extract and all but chloroform fraction. Flavonoids and steroids were present in all except n-Butanol fraction. Saponins were detected in only methanol extract and n-Butanol fraction while terpenoids were not present in n-Hexane, chloroform and n-Butanol fractions. Anthraquinones, coumarins, quinones and xanthoproteins were not confirmed in all fractions and extract.  Quantitative analyses revealed a significant difference (p < 0.05) in the contents of the total phenolics and total flavonoids in the fractions when compared to the methanol extract. The leaf extract and fraction's ability to scavenge free radicals against 1,1-diphenyl-2-picrylhydrazyl (DPPH) demonstrated a concentration-dependent percentage inhibition. However, the methanol extract, n-Butanol and ethyl acetate fractions were most effective of all the fractions. This study has demonstrated the different fractions and methanol extract of Ficus platyphylla leaves can explored in the management of oxidative stress related complications in mammals.
Keywords: Antioxidants; Ascorbic Acid; DPPH; Ficus platyphylla; Free radicals; Phytochemicals